Long term conservation agriculture impact on soil nitrogen fractions and wheat (Triticum aestivum) yield in subtropical Inceptisol - THAMMAIAH, MOHANKUMAR KARADIHALLI; SHARMA, VINOD K; PARIHAR, CHITER M; BARMAN, MANDIRA; DEY, ABIR; CHAKRABORTY, DEBASHIS (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at ICAR-Indian Agricultural Research Institute (IARI), New Delhi over two consecutive years (2020 and 2021) to evaluate the influence of conservation agriculture (CA) and nitrogen management strategies on wheat yield in an intensified maize (Zea mays L.)-wheat (Triticum aestivum L.)-mungbean (Vigna radiata L.) cropping system. Results indicated that grain and straw yields of wheat in CA plots were higher, reaching 4829 and 7231 kg/ha, respectively. However, these yields were statistically comparable to those obtained from conventionally tilled plots (4502 and 6611 kg/ha, respectively). Significantly higher wheat grain and straw yields were observed in plots receiving nitrogen fertilizer. Interestingly, the harvest index remained unaffected by both tillage practices and nitrogen management strategies. After two seasons of wheat cultivation, CA plots had significantly higher soil nitrogen fractions, including mineral, alkali-permanganate, potentially mineralizable, microbial biomass N and total nitrogen, compared to conventionally tilled plots. Moreover, all nitrogen-receiving treatments demonstrated significantly higher nitrogen fractions at both soil depths (0–5 and 5–15 cm) compared to the control. Notably, plots treated with urea super granules exhibited superior results in enhancing plant-available nitrogen. In conclusion, this study underscores the importance of CA and various nitrogen management strategies for increasing wheat crop yield and promoting plant-available nitrogen fractions in the soil. These findings providevaluable insights for farmers and researchers looking for sustainable and efficient agricultural practices to optimize wheat production and soil health.